The Influence of Grammar and Vocabulary Mastery Towards Students’ Recount Writing Text - Tia Karlina; Gola Kusnarti (Riviera Publishing, 2024)
The purpose of this research was to determine the influence of grammar and vocabulary mastery during learning process towards students’ recount writing text, the influence of grammar mastery towards students’ recount writing text, and the influence of vocabulary mastery towards students’ recount writing text. The total sample of this research is 100 students by using samole – random – sampling. This research conducted at Private Vocational Schools in Cirebon, namely SMK Mandiri and SMK Bakti Persada. To collect the data, the students were given 50 questions about grammar in the multiple choice and for vocabulary mastery the students were also given 50 questions about vocabulary. The result of this research indicated that: 1) There are significant influence of grammar and vocabulary mastery towards students’ recount writing skill at private vocational school in Cirebon Regency. It is proved by the Sig 0.000 < 0.05 and the value of Fo = 94.129. 2) There is a significant influence of grammar mastery towards students’ recount writing skill at private vocational school in Cirebon Regency. It is proved by the Sig 0.000 < 0.05 and the value of to = 2.498. 3) There is a significant influence of vocabulary mastery towards students’ recount writing skill at private vocational school in Cirebon Regency. It is proved by the Sig 0.000 < 0.05 and the value of to = 10.792. It can be said that the students’ recount writing skills at private vocational school in cirebon regency is significally influence by grammar and vocabulary mastery.